ANALISIS KINERJA EVAPORATOR PADA VAPORS COMPRESSION REFRIGERATION SYSTEM MENGGUNAKAN REFRIGERANT R410A - Sukarman Sukarman; Khoirudin Khoirudin; Murtalim Murtalim; Ahmad Fauzi; Ricko Valderama; Amri Abdulah; Anwar Ilmar Ramadhan (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2022)
VCR system is an energy conversion device that uses a mechanical vapour compression cycle in the process. The performance of the VCR system using environmentally friendly refrigerants is a significant issue, and much research is still underway to evaluate and improve the efficiency of the systems used. Therefore, this paper presents an experimental investigation of the performance of the refrigeration cycle. A VCR system was used as a test tool. The coefficient of performance (CoP) was studied using a VCR system design with varying evaporator loads. Variation of an evaporator load is done by intervening fan rpm at five rpm levels. The VCR system uses a compressor with a capacity of 365 watts using R410A refrigerant. Refrigerant R410A is one of the alternative refrigerants to replace R22 which is not environmentally friendly. Experimental data was validated using Genetron Properties 1.1 software. Experimental analysis data showed that the highest CoP was obtained at the lowest rpm with a value of 3.17. Meanwhile, the lowest CoP is 3.02, obtained at the highest rpm. Loading the evaporator with fan rpm produces a CoP value indirectly proportional to the fan rpm value. Genetron 1.1 software validation results produce a higher CoP value of about 2%-3% than experimental data.